Toxicity mechanisms and remediation strategies for chromium exposure in the environment - Yan, Guangwei; Gao, Yingjun; Xue, Kun; Qi, Yijian; Fan, Ying; Tian, Xue; Wang, Jinji; Zhao, Renyu; Zhang, Pu; Liu, Yongxia; Liu, Jianzhu (Frontiers in Environmental Science, 2023)
Chromium (Cr) is the seventh most abundant chemical element in the earth’s crust, and Cr(III) and Cr(VI) are common stable valence states of Cr. Several Cr-containing substances, such as FeOCr2O3 and stainless-steel products, exist in nature and in life. However, Cr(VI) is toxic to soil, microorganisms, and plants and poses a serious threat to human health through direct and indirect exposure. By collecting published journal literature, we found that Cr(VI) can cause acute and chronic toxicity in organisms and has carcinogenic effects, and the mechanisms causing these toxicity include endoplasmic reticulum stress, autophagy and apoptosis. However, the relationship between these mechanisms remains unclear. Many methods have been researched to purify chromium, but each of these methods has its own advantages and disadvantages. Therefore, this review summarizes the hazards of chromium and the mechanisms of chromium toxicity after entering cells and provides a number of methods for chromium contamination management, providing a direction for the next step in chromium toxicology and contamination decontamination research.